Foto reportaje del lenguaje no verbal del arte marcial ecuatoriano Sojukay - Tipantuña Tipantuña, Alex Daniel (2016)
This degree work is the development of a photo essay on the martial art Sojukay, to publicize how the Ecuadorian cultural identity is expressed its practice, by analyzing nonverbal communication. According to the fundamentals of structuralism, cultural identity can be understood through the study of the elements that compose it, in this case Sojukay, and the relationships between them, constantly changing. The same applies to non-verbal communication, which can be understood through its subsystems and indicators that these contemplated, without losing sight of the totality takes on different features of the characteristics of the individual elements. Then, in order to achieve the overall goal set, it was first conducted a research process, through which the relationship between cultural identity and nonverbal communication, within the context of Sojukay were explained; and the meanings that acquires in that environment the main body movements, facial expressions, distance between practitioners, clothing and use of weapons / tools were determined. As a result, photojournalism proved to be a way to reflect the circular movements of hands and arms (top, middle and bottom), the torso, and the lateral, diagonal and vertical movement of legs and feet, which, together with a facial expression calm and relaxed, variations in distance between the athletes and the use of costumes and warlike weapons, means self-control, cultural belonging to the Ecuadorian nation and capacity for self-defense.